2021
DOI: 10.1515/biol-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

miR-338-3p inhibits cell growth, invasion, and EMT process in neuroblastoma through targeting MMP-2

Abstract: This study aimed to explore the regulatory mechanisms of miR-338-3p and matrix metalloproteinase-2 (MMP-2) in neuroblastoma. Putative target interaction regions of miR-338-3p on MMP-2 were predicted by miRcode and miRbase bioinformatics tools. Relative expression of miRNA-338-3p and MMP-2 in neuroblastoma tissues and GI-LI-N and SK-N-SH cells was determined by reverse transcription polymerase chain reaction experiment. Furthermore, the cell proliferation was determined by Cell Counting Kit-8 assay, the cell ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Thus, the enrichment of these pro-tumor ECM remodelers in the highly invasive M1 cells is potentially responsible for inducing a metastasis-favorable microenvironment at the secondary sites, thereby promoting the colonization of the injected M1 cells. Furthermore, previous studies have shown the oncogenic potential of MMP2/9 in HR-NB cell lines in vitro [58][59][60]; thus, M1 cells provide an opportunity to explore additional, previously unidentified MMPs in HR-NB and their implications in NB-TME in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the enrichment of these pro-tumor ECM remodelers in the highly invasive M1 cells is potentially responsible for inducing a metastasis-favorable microenvironment at the secondary sites, thereby promoting the colonization of the injected M1 cells. Furthermore, previous studies have shown the oncogenic potential of MMP2/9 in HR-NB cell lines in vitro [58][59][60]; thus, M1 cells provide an opportunity to explore additional, previously unidentified MMPs in HR-NB and their implications in NB-TME in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of "cell junction assembly" as an important biological process in ACC metastasis highlights the signi cance of cell adhesion and interactions in cancer progression. In numerous cancer types, including pancreatic cancer (55) and pancreatic cancer (56) tumor spread and invasion have been shown to be aided by the breakdown of cellular junctions. Cell connection disruption may encourage the spread of tumor cells and their in ltration into neighboring tissues (57).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) is linked to a variety of cancer-related activities, including tissue invasion and metastasis [ 58 ]. MiR-338-3p was confirmed to suppress EMT pathway in neuroblastoma cells by targeting matrix metalloproteinase-2 (MMP-2) [ 59 ]. Reduced expression of miR-146b-5p in T-cell precursor ALL resulted in the up-regulation of IL17A, which promotes cell migration and invasion [ 60 ].…”
Section: Implication Of Mirnas In Carcinogenesis and Leukemogenesismentioning
confidence: 99%